Growth differentiation factor 15: a promising biomarker in oral cancer - Oh, Hyun Jun; Lee, Jong-Ho; Kim, Soung Min (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2025)
Growth differentiation factor 15 (GDF-15), a cytokine within the transforming growth factor-β superfamily, is involved in various malignancies, with implications in oral squamous cell carcinoma (OSCC). Elevated GDF-15 levels are correlated with unfavorable prognosis, tumor progression, and chemotherapy resistance, and the protein has been identified as a potential diagnostic and prognostic biomarker for OSCC. Personalized treatment strategies based on GDF-15 expression could improve treatment outcomes.